3D printing concrete with recycled coarse aggregates: The influence of pore structure on interlayer adhesion. (November 2022) - Liu, Huawei; Liu, Chao; Wu, Yiwen; Bai, Guoliang; He, Chunhui; Yao, Yizhou; Zhang, Rongfei; Wang, Youqiang
Abstract: Concrete digital fabrication technology has been rapidly emerging while facing sustainability issues due to the high cement proportion in printed materials, rendering an environmentally friendly material design containing coarse aggregates one way for the concrete 3D printing industry to achieve more sustainable development. Here, 3D printed concrete with recycled coarse aggregate (RCA) was prepared, and its interlayer bonding properties were investigated considering different RCA replacement ratios, interlayer time intervals and layer heights. The results showed that RCA and the printing time interval degraded the interlayer bond strength, whereas no clear correlation was found with the layer height. Although the incorporation of RCA significantly changed the interlayer bonding system and cracking pattern, the interlayer bond strength of 3D printed recycled coarse aggregate concrete was substantially higher than that of 3D printed mortar. Finally, focusing on the pore structure characteristics, the mechanism influencing the interlayer bond performance is discussed.